Trends in Childhood Underweight in Norwegian Children: Data From Routine Child Healthcare, 2010–2022 - Sara‐Rebekka Færø Linde; Roy Miodini Nilsen; Mathieu Roelants; Melissa R. Balthasar; Jennifer L. Baker; Dorthe C. Pedersen; Boye Welde; Marjolein M. Iversen; Petur B. Juliusson; Anne‐Siri Fismen (Acta Paediatrica, 2026)
ABSTRACT Aim This study examined age‐ and sex‐specific prevalence and trends in underweight among Norwegian children and adolescents during the pre‐pandemic period from 2010 to 2019 and COVID‐19 pandemic period from 2020 to 2022. Methods Height and weight data from 78 024 children aged 2 to 13 years in Bergen from 2010 to 2022 were obtained from public health clinic and school health service records. Underweight grades 1 to 3 were defined using the International Obesity Task Force cut‐offs. Age‐ and sex‐specific prevalence was analysed longitudinally, and trends were assessed for boys and girls across age groups using regression analyses. Results Underweight was most prevalent among 2‐year‐olds and declined with increasing age, more in girls than boys. Among girls, the prevalence decreased from 19.3% at age 2 years to 6.2% at age 13 years, and among boys from 13.3% to 8.6%. The interaction between sex and age was statistically significant. During the pre‐pandemic period, prevalence decreased significantly among 2‐year‐olds. During the pandemic period, increased prevalence of underweight was observed among 8‐year‐old girls. Conclusion Underweight remains a relevant public health concern, with clear age‐ and sex‐specific patterns. These findings highlight the need for continued monitoring and targeted follow‐up in early childhood.